Designing Numeracy Literacy Assessment Media for High School Using Formative Websites on Rectilinear Movement Material - Novita, Vernanda Dela; Ekawati, Elvin Yusliana (Universitas Negeri Semarang, 2025)
There needs to be innovation and creativity from educators in designing assessment processes that support learning, one of which is through the use of digital media. In physics learning which often involves abstract concepts and numeracy skills an engaging and up-to-date assessment strategy is necessary. This study aims to develop a website-based Formative assessment media to measure students' initial numeracy literacy in Straight Motion material. The research uses the ADDIE model with five stages: analysis, design, development, implementation, and evaluation. The media includes a home page display and interactive questions aligned with numeracy literacy indicators. Expert validation obtained a score of 16 out of 20 for material aspects and 18 out of 20 from the second validator for media aspects. The media also received a score of 81 out of 84 for appearance and 80 out of 84 for content from a second validator. These findings indicate that the Formative-based website media meets the